Cystoseira abies-marina life cycle : comparative study of its polar profile by RP-HPLC-DAD-MS - Seca, Ana M. L. (2016)
Macroalgae, are largely used in food, pharmaceutical and cosmetics industries. Cystoseira abies-marina (S.G. Gmelin) C. Agardh is a brown macroalgae (Phaeophyta) which belongs to Cystoseira genus and is distributed in the Mediterranean, Macaronesian Region and the coast of Africa. In the Azores lslands, it grows abundantly in the intertidal zone where it is pioneer and attains large size. Since intertidal seaweeds are exposed to extreme stress conditions (temperatura, UV, water levei) in addition to herbivory and fouling, they develop protective mechanisms, some of which involve the biosynthesis of metabolites with properties that may be useful to man (e.g. natural antioxidants, antifouling agents, novel UV sunscreens). The dichlormethane extract of C. abies-marina from Azares was studied revealing the presence of meronorditerpenoids with cytotoxic and antioxidant activities. In this research the antioxidant activity and chemical composition of the ethyl acetate fraction of C. abies-marina methanolic extract was studied. C. abies-marina was collected in two phases of its life cycle üuvenile phase and mature phase). […].